Freemason and Philanthropist: The Case of Edouard Jonniaux and the Masonic Concerts in Brussels (1861–86). (15th September 2017) - Vergauwen, David
Abstract : The philanthropic activities of Edouard Jonniaux are indicative of the ways freemasons in Brussels mobilized the musical potential of their lodges to compete with Catholic charities. Jonniaux considered it a masonic obligation for the musicians of the capital's lodges to perform for the latter's philanthropic endeavours. As charity concerts were frequently being performed in churches, the Brussels masons decided to open up their lodge rooms for similar concerts and when this venue proved to be too small, they happily used the capital's royal theatre, i.e. the national opera house where they had privileged connections. Especially during the 1860s, Brussels freemasonry was actively recruiting musicians, not the amateurs, but the professional ones. In order to integrate those talented musicians into the lodges, Jonniaux personally watched over their rights and supported free membership for musicians. All this resulted in many concerts that often served as a propaganda tool for the liberal and anticlerical cause.